A review on use of escape rooms in education – touching the void. Issue 2 (3rd April 2022) - Taraldsen, Lene Hayden; Haara, Frode Olav; Lysne, Mari Skjerdal; Jensen, Pernille Reitan; Jenssen, Eirik S.
ABSTRACT: This review article focuses on use of an escape room as a didactic tool in teaching and learning, as identified in empirical studies that have examined the use of escape rooms in educational contexts. The review studied the methods used to study escape rooms, what the focus of attention was, what the reported use was, and implications this has for the use of escape rooms for teaching and learning. Our analysis showed that most studies are concerned with the implementation and use of an escape room in relation to four fields of attention; scenario, curriculum, 21st-century skills, and motivation. Overall, the reviewed articles indicate that more studies are needed on the use of escape rooms for educational purposes. It seems that research on this topic has reached a new phase, and there is a need for structured research and transparency in the research design and methods for data collection and analysis. We see opportunities for the use of escape rooms as a didactic tool in primary and secondary education, and in teacher education.